A study of biofilm production in clinical isolates of Staphylococci at a tertiary care hospital, Bangalore - Golia, Saroj; B, Asha S. Kamath; AR, Nirmala (International Journal of Research in Medical Sciences, 2017)
Background: The Biofilms are densely packed communities of microorganisms consisting of layers of cell clusters embedded in a matrix of extracellular polysaccharide called polysaccharide intercellular adhesin. This layer impedes the delivery of antibiotics to the biofilm forming microbial cells leading to emergence of drug resistance. Staphylococci are commensal bacteria on the human skin and mucous membranes. So it may be easily introduced as a contaminant during the surgical intervention. So, this study was conducted to identify the Biofilm producing strains from clinical isolates of Staphylococci. Methods: A total of 182 non-repetitive clinical strains of Staphylococci isolated from various clinical samples from Feb 2014 to Oct 2014 were included in the study. All the isolates were identified using standard microbiological procedures. All the samples were tested for biofilm production by modified Congo-red agar method and tube method. Results: Out of 182 samples that were included in the study, a total of 90 (49.45%) samples showed biofilm formation of which 58 (75.32%) were methicillin resistant and 32 (30.47%) were methicillin sensitive. Also these strains were resistant to other antibiotics. Conclusion: Our study showed biofilm production by methicillin resistant strains which were also multidrug resistant. Treatment of methicillin resistant strains of Staphylococci is one of the most challenging task for the clinicians and the microbiologists. So they should be routinely screened for biofilm formation in order to prevent emergence and spread of multidrug resistant strains.